Effects of Self-Assisted Manual Therapy Combined with a High-Intensity Walking Program on Musculoskeletal Pain, Functionality, and Posture in Older Adults: A Multicentre Randomized Controlled Trial - Gemma Victoria Espí-López; Laura Fuentes-Aparicio; Rocío Cogollos-de-la-Peña; Lucas Monzani; Elena Marques-Sule; Dagmar Pavlu; Anna Arnal-Gómez (Life)
Background: Aging is associated with musculoskeletal pain and postural adaptations which may affect functionality. This study aims to analyse the effect of a combined protocol of self-assisted manual therapy and high-intensity walking on musculoskeletal back pain, functionality, and shoulder posture in older adults, and to establish the short- and medium-term effects of this program. Methods: A multicentre, double-blind, randomized trial was conducted on older adults. The sample was divided into two groups: the self-assisted manual therapy plus walking at high-intensity group (MTWG) and the Control Group (CG), with the latter undergoing supervised high-intensity walking only. Pain (Pressure Pain Threshold and Visual Analogue Scale), functional capacity (5-times sit-to-stand test), and change in thorax position (acromion position) were assessed at T0 (baseline), T1 (after 4-week intervention) and T2 (follow-up, 4 weeks after the end of the intervention). Results: A total of 95 older adults (41 in the MTWG and 54 in CG) completed the study and were analyzed. After isolating the effect of correlations among our primary outcomes, our analysis revealed statistically significant between-subject (p < 0.01), within-subject (p < 0.001) and between-within subject differences (p < 0.05) in Pressure Pain Threshold scores in favour of the MTWG. We also detected within-subjects (p < 0.001) and between-within subject differences (p < 0.05) in scores for the Visual Analogue Scale, in favour of the MTWG. These patterns of results remained stable at T2. The 5-times sit-to-stand test (p < 0.01) and the acromion position (p < 0.05) improved at T1 for the MTWG but not at T2. Conclusions: A combined protocol of self-assisted manual therapy and high-intensity walking, compared to high-intensity walking alone, improved musculoskeletal pain, functionality, and posture in older adults in the short term (over one month), with pain reduction maintained in the medium term (at the one-month follow-up).